Factors influencing young women's entrepreneurial performance in Malaysia - Sabura binti Mustapa
Entrepreneurship among young women is recognised as an important driving force in fostering the economic growth of a country. However, it has been reported that most businesses operated by young women perform poorly due to several reasons. This study aims to identify the factors contributing to the entrepreneurial performance of young female entrepreneurs in the Klang Valley, Malaysia. Questionnaires were used as a method of data collection and 231 structured questionnaires were distributed to young female entrepreneurs who are running businesses and residing in the Klang Valley. All of the respondents are registered under the Company Commission of Malaysia. The collected data was analysed using SPSS Version 22.0. In general, the results of the multiple regression analysis show the factors influencing the performance of young female entrepreneurs. These factors include sufficient motivation, training support as well as financial support provided to them. The findings also reveal that motivation is the most important factor that contributes to the entrepreneurial performance of young female entrepreneurs. The findings of this research are helpful to related government agencies and authorities to identify the proper tools and strategically plan relevant programmes to enhance the performance of young female entrepreneurs in the context of the Malaysian business climate.